The Influence of Good Corporate Governance, Company Size, Capital Structure and Company Growth on the Financial Performance of Retail Companies Listed on the IDX: Pengaruh Good Coorporate Governance, Ukuran Perusahaan, Struktur Modal dan Pertumbuhan Perusahaan Terhadap Kinerja Keuangan Perusahaan Retail yang Terdaftar di BEI - Kibtiyah, Mariatul; Maryanti, Eny (Universitas Muhammadiyah Sidoarjo, 2022)
Financial performance is one of the concerns that is the focus of company management in making choices related to the implementation of company activities. The purpose of this research is to know whether the variables of GCG, company size, capital structure and company growth affect the company's financial performance. Purposive sampling is a sampling technique taken to determine the sample in this research so that this study found a sample of 11 companies in the retail sector so that the total sample taken for 3 years from 11 companies is 33 companies then secondary data which is the source of data in the study This is tabulated and processed with the help of SPSS version 25 then a set of test tools to support the hypothesis with a partial t-test. That the results obtained in this analysis are that the company's performance is proven to be able to be influenced by good corporate governance, the company's performance is proven to be unable to be influenced by the size of the company, the company's performance is proven to be unable to be influenced by the capital structure and the company's performance is proven to be unable to be influenced by the company's growth. The determination test is worth 0 57.9% then the remaining 42.1% in this study can be explained by variables that might affect the company's performance which were not carried out in this research.